Exhaust emissions analysis of gasoline motor fueled with corncob-based bioethanol and RON 90 fuel mixture - Widiyanti, Widiyanti; Mizar, Muhammad Alfian; Wicaksana, Christian Asri; Nurhadi, Didik; Moses, Kriya Mateeke (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2019)
One of the viable solutions to the fossil fuel energy crisis was to seek alternative sources of environmentally friendly energy with the same or better quality such as bioethanol. It was possible to produce bioethanol from organic waste, e.g., corncob. This research aimed to obtain the lowest exhaust emission levels of CO and CO2 generated from a gasoline motor that used a mixture of bioethanol containing 96 % corncob and RON 90 fuel. This research was experimental using Anova statistical data analysis method. The results showed that the lowest average of CO emissions was 0.177 vol% using E100 fuel, and the highest average was 2.649 vol% using 100 % RON 90 fuel, displaying a significant difference. The lowest average of CO2 emissions was 6.6 vol% using E100 fuel, and the highest was 7.51 vol% using 100 % RON 90 fuel, which was insignificantly different. The mixture variation with the lowest CO and CO2 emissions was E100.